Determining the Ecological Citizenship Levels of Tourism Students: The Case of Eskişehir, Turkey - Çiçek, Dönüş; Gülenç, Seher; Korkmaz, Erdem (Journal of Tourism, Sustainability and Well-being, 2024)
We live in an era dominated by major environmental issues, for which countries try to bring solutions considering the philosophy of sustainability. As a concept concerning all humanity, ecological citizenship is regarded as an action to be taken to solve these problems. It is crucial for tourism students, who are prospective human resources for tourism industry, to have environmental awareness and act accordingly. This study aims to determine the ecological citizenship levels of tourism students, and their ecological citizenship level is analysed in terms of various factors. This study was designed with a correlational survey model, one of the quantitative research methods. The study group includes tourism students from Anadolu University and Eskisehir Osmangazi University in Eskisehir, enrolled in the 2022-2023 academic year. An “Ecological Citizenship Scale” was utilised in order to gathering data. The results of this study showed that tourism students had medium-level ecologic citizenship awareness. When considered in terms of variables/parameters, differences were found among all variables and dimensions. Finally, the students stated that the first three significant factors that had an influence on their ecological citizenship levels were family, education, and social media.